UNVEILING THE ROLE OF WORKPLACE ENVIRONMENT IN ACHIEVING THE SUSTAINABLE DEVELOPMENT GOAL EIGHT (SDG8) AND EMPLOYEE JOB SATISFACTION POST-PANDEMIC: PERSPECTIVE FROM AFRICA - Timilehin Olasoji OLUBIYI (Management & Marketing)
Sustainable Development Goal 8 on decent work for all combines social, economic, and environmental objectives. Yet the significance of Goal 8 and other goals of the United Nations is receiving less attention in Africa. More so due to the dynamic character of the environment in the modern era, particularly post-COVID-19 pandemic businesses are faced with a variety of obstacles and employee dissatisfaction is increasing in the workplace. Therefore this study investigates the effects of the workplace environment on employee job satisfaction in selected listed banks and their role in achieving SDGs in Nigeria, the most populous country in Africa and the largest economy. This investigation utilized a survey research design. For this study, three (3) out of the twelve(12) banks listed on the Nigerian Stock Exchange(Nigeria Exchange Group) as of 31st July 2023 were selected from the population. A total of 495 copies of the questionnaire were distributed using Google Forms, and a response rate of one hundred per cent was attained. Findings showed that workplace environment had a significant and positive effect on employee job satisfaction. The findings revealed that workplace environment had a significant effect on employee job satisfaction of selected listed banks in Nigeria. The study recommends that the management of Nigerian listed banks should ensure that employees are well compensated according to industry best practices.